Pengaruh Kompetensi dan Budaya Organisasi terhadap pengembangan Karyawan pada Kantor PT Midi Utama Indonesia Tbk Branch Makassar - Fajrul Bahtiar; Azhary Ismail; Baharuddin Baharuddin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of competence and organizational culture on employee development at PT. Midi Utama Indonesia Tbk Branch Makassar. Competence refers to the skills, knowledge, and attitudes possessed by employees, while organizational culture refers to the values, norms, and practices within the company. Employee development is the company's efforts to improve the quality of human resources through training, education, and career opportunities. This research uses a quantitative approach with a survey method, where data was collected through questionnaires distributed to employees at the Makassar branch. Data analysis was conducted using multiple regression techniques to test the simultaneous effect of competence and organizational culture on employee development. The findings indicate that to enhance employee development, PT. Midi Utama Indonesia Tbk Branch Makassar needs to focus on improving competence through appropriate training and fostering an organizational culture that supports innovation and learning. This study provides recommendations for the company to better optimize development programs that focus on competence and a positive work culture to improve employee quality.